Saccade-related LFP power transients in the primate amygdala and hippocampus linked to the perception of social status - Seung Hyun Lee; Hanga Dormán; Zoltan Nádasdy; Katalin M. Gothard (Proceedings of the National Academy of Sciences, 2026)
A key aspect of healthy social functioning in both humans and nonhuman primates is the ability to extract status-related information from observing the social signals exchanged between individuals. Knowing the social status of others determines how long we look at them and how we engage with them in social interactions. While looking at faces and eyes requires a functionally intact amygdala, hippocampal memories guide the eyes toward socially relevant areas of a visual scene. We examined the local field potentials associated with socially meaningful eye movements in the amygdala and hippocampus of macaques as they watched videos of dominant–subordinate interactions among unfamiliar conspecifics. In both structures, the saccade-related potentials showed status-dependent amplitude modulation in specific frequency bands. In the amygdala, shifting gaze from lower- to higher-status individuals was associated with anticipatory power transients in the 20 to 25 Hz frequency band, whereas gaze shifts from higher- to lower-status individuals were marked by predominantly postsaccadic power transients. Following the gaze of the aggressive, dominant individual induced increased postsaccadic power in the gamma band in both the amygdala and hippocampus, with some variation in frequency depending on whether the saccade landed on the social partner or elsewhere. The timing, frequency, and status-specificity of these power transients reveal the contribution of the amygdala and hippocampus to the visual exploration of social scenes.